Potential negative effects and heterogeneous distribution of a parasitic copepod Salmincola edwardsii (Copepoda: Lernaeopodidae) on Southern Asian Dolly Varden Salvelinus curilus in Hokkaido, Japan. - Hasegawa, R., C.G. Ayer, Y. Umatani, K. Miura, M. Ukumura, H. Katahira & I. Koizumi (Parasitology International, 2022)
The genus Salmincola is an ectoparasitic copepod group commonly infesting the branchial and buccal cavities of salmonids. While negative impacts on hatchery fishes have been reported, their impacts on wild fish populations and distribution patterns are critically understudied. In the Shiretoko Peninsula, Hokkaido, Japan, we found parasites belonging to this genus on the branchial cavity of a stream salmonid, Southern Asian Dolly Varden Salvelinus curilus. All parasites recovered were identified as Salmincola edwardsii based on morphological characteristics and partial 28S rDNA sequences. Prevalence was highly heterogeneous even among neighboring streams (0-54.8%, < 10 km) with the mean intensity among streams being generally low (2.19 parasites/infeted fish). Despite the low intensity, quantile regression analysis showed negative trends between parasite intensity and host condition, suggesting that the infestation of S. edwardsii has a potential negative impact on the host salmonid. In addition, a single copepod was found from an anadromous fish, which could indicate some salinity tolerance of the copepods. It is important to evaluate the effects of Salmincola spp. on host species and determine the limiting factors on the parasite's distribution for proper management.